Impact of the Mindful Emotional Intelligence Program on Emotional Regulation in College Students - Héctor Enríquez (International Journal of Psychology and Psychological Therapy, 2017)
The present study tests the effectiveness of the Mindful Emotional Intelligence Program PINEP that appeared from the fusion of two concepts emotional intelligence and mindfulness. The program was given as training to 136 college students during a two-month period. The purpose of the study was to determine the impact of PINEP and to now how students regulate their emotions. Student emotional behavior was evaluated before and after the PINEP program was carried out using self-report measures selected for their reliability. These were, burnout, engagement, neuroticism, extroversion, emotional reulation and empat. e results soed moderate sinicant differences Coens d in the dimension of extroversion, burnout, engagement, refocus on planning, positive reappraisal, putting into perspective and empathy. The outcome pointed toward favorable changes in relation it te proram NE as te students soed sinicant canes in te a te reulated teir emotions after the training.